Analytical screening of marine algal toxins for seafood safety assessment in a protected Mediterranean shallow water environment. Issue 4 (3rd April 2019) - Mattarozzi, Monica; Cavazza, Antonella; Calfapietra, Anna; Cangini, Monica; Pigozzi, Silvia; Bianchi, Federica; Careri, Maria
ABSTRACT: Microalgal species growing in marine and aquaculture environments can be responsible for harmful events because of their ability to produce potent natural toxins that can accumulate in edible mollusc species. Their consumption can cause severe illness and even be lethal. The European Union provides comprehensive regulations covering various general food safety aspects to manage the risk of contamination in shellfish farms. Many analytical methods have been proposed to evaluate algal toxins presence in the environment and in food products, for conducting surveillance studies of the main molluscs production sites and, where necessary, immediate monitoring of possible contamination of shellfish. In this work, a one-year analytical surveillance study was carried out to verify the possible presence of algal biotoxins in molluscs from a Mediterranean breeding area. Water and molluscs were sampled from a district of the North-East coast of Sicily, consisting of a unique brackish ecosystem of two lakes connected to each other and to the sea by narrow canals. Water samples were collected to investigate phytoplankton i by microscope analysis to assess the presence of potentially toxin-producing species, such as Pseudo-nitzschia spp, Alexandrium spp and Gonyaulax spinifera, although the presence of toxic phytoplankton has never reached alert levels. Mussels and clams samples were submitted to analysis of paralytic shellfish poisoning toxins, amnesic shellfish poisoning toxins and lipophilic toxins by liquid chromatography-based methods Only a few yessotoxins were detected, having concentrations always below the regulation limits. An existing liquid chromatography-tandem mass spectrometry-based multiresidue method for lipophilic biotoxins was adopted and extended to cover emerging biotoxins such as cyclic imines. The performance of the analytical method for Gymnodimine A and Spirolide 13-desMeC was assessed, obtaining respective quantitation limits of 20 and 10 µg kg −1, a precision always lower than 13% and trueness in the 81–120% range. Method applicability was confirmed using certified materials and a naturally contaminated sample. Graphical Abstract: